Seesaw: An Interactive Display to Facilitate Social Interaction. (2015) - Yang, Chulin; Wang, Stephen Jia
Abstract: This paper introduces Seesaw an interactive environment prototype that assists children to conquer common/potential fear during social communication in order to facilitate interactions that provide enhanced group-learning activities. Based on the games studies which emphasize children's psycho-behavioral and cognitive aspects, Seesaw aims at lowering the mental fears among 3-8 year old children, hence facilitating their social behavior. This prototype uniquely combines virtual reality and multi-touch technology. The design has been based mainly on the methodologies of tangible interaction design.